Hotel Cost Savings and/or Travel Experience? - Dr Mondok, Anita (Jelenkori Társadalmi és Gazdasági Folyamatok, 2023)
In countries dependent on external resources, utility prices have risen significantly, with the accommodation sector also strongly affected. In addition, guests are becoming increasingly demanding in terms of the overall guest experience. In addition to examining the general cost-saving practices of domestic hotels, this article focuses on Hungarian wellness hotels, assessing the proportion of operators who have opted for temporary or permanent closure. In addition to the practical solutions of the hotels, the article presents the results of in-depth interviews, focusing on the hotel market in Debrecen, which with its complex offer is also representative of the national trends. Although a wave of hotel closures was predicted during the autumn of 2022, the era of closures did not happen due to the external environmental factors supporting the sector to the extent that operators persisted with their continuous operation However, it remains questionable how many operators can stay in the market in the long term.